Numerical Simulation Of Self-Alignment Of Chip Resistor Components For Different Silver Content During Reflow Soldering - Abdullah, Mohd Zulkifly; Ali Mokhtar, Mohd Najib; Saad, Abdullah Aziz; Samsudin, Zambri; Che Ani, Fakhrozi (Elsevier Ltd., 2017)
Three-dimensional simulation and experimental investigation of self-alignment phenomena during the reflow soldering process were presented. The multiphase flow model was developed using ANSYS Fluent to investigate the self-alignment effect of laminar melted lead-free solder during the reflow phase on board. User-defined function with c-code was integrated into the model, Volume of Fluid (VOF) method was applied to the melt front tracking, and solidification model was used for the phase change solder material. The material used in the study was SAC 105, SAC 305 and SAC 405. The specific heat, latent heat, solidus temperature, liquidus temperature of the lead-free solder and geometrical data for model input was determined experimentally. The model was validated experimentally. The self-alignment capability of different lead-free solder was presented. It has been observed that higher silver content solder (SAC 405) have higher self-alignment capability during reflow soldering compare to SAC 305 and SAC 105. Moreover, all cases show self-alignment in perpendicular to the longer sides of chip resistor travelled more towards the central position. The experimental and simulation results are in good conformity and can be extended for different cases.